Motivasi dan Tantangan Pengusaha Wanita: Studi Desa Budaya Dayak Pampang - Fenty Fauziah; Mursidah Nurfadillah; Bun Yamin; Ade Gunawan (Universitas Winaya Mukti, 2022)
Opportunities and challenges and for women to contribute to economic growth, which can be started from micro-enterprises, expecialy for East Kalimantan as a new candidate national capital. The study analyzes the motivational factors and challenges of women entrepreneurs who run businesses in the cultural village of Pampang, East Kalimantan. Using a qualitative methodology based on in-depth interviews, providing insight into the entrepreneurship of 10 women in the Pampang cultural village when starting entrepreneurship and managing their businesses. Informans are engaged in various fields related to culture such as producing beads and selling Dayak handicrafts. The results showed that preserving the Dayak culture was the main motivation for starting a business. The challenges faced by women entrepreneurs come from informal and formal institutions. A significant challenge faced by women entrepreneurs is that their abilities as professional entrepreneurs are not recognized by the community. Informans faced emerging challenges in other aspects of the business, such as procuring finance, creating networks, and managing employees. Challenges related to formal institutions such as the lack of quality education and changes in government policies that prohibit holding meetings during the COVID-19 pandemic have reduced the number of tourists who come to the Pampang tourist village, resulting in reduced income.